2010
DOI: 10.1007/s12034-010-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Nb-doped ZnO transparent conductive thin films deposited by rf magnetron sputtering using a high quality ceramic target

Abstract: Nb-doped ZnO films with (002) orientation have been grown on glass substrates by rf magnetron sputtering followed by vacuum annealing at 400°C for 3 h. The microstructures and surface figures of the Nbdoped ZnO films were investigated with X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. And its optical and electrical properties were measured at room temperature using a four-point probe technique and 756-type spectrophotometer, respectively. X-ray diffraction (XRD) revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is reported that a widening of the band gap and a blueshift of the optical absorption edge occur with the increase of Nb contents [6,11] , which is contradictory to the results in Ref. [12]. Moreover, it is well known that the band structure of ZnO may change with the strain field, which subsequently modifies the optical and electrical characteristics.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…It is reported that a widening of the band gap and a blueshift of the optical absorption edge occur with the increase of Nb contents [6,11] , which is contradictory to the results in Ref. [12]. Moreover, it is well known that the band structure of ZnO may change with the strain field, which subsequently modifies the optical and electrical characteristics.…”
Section: Introductionmentioning
confidence: 66%
“…Nb-doped ZnO is grown on relaxed Zn 1x Mg x O substrate by epitaxial growth, the magnitude of stress is characterized by the Mg content of Zn lx Mg x O, The greater the Mg content is, the larger the stress is. ZnO, Zn lx Mg x O and Zn 1y Nb y O crystallize and belong to the hexagonal wurtzite structure with Mg and Nb content less than 30% [9,[12][13][14] . The ZnO/ Zn lx Mg x O shows better crystalline quality and ultraviolet emission performance, smaller strains and higher transmittance in the visible range [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…Doping of Nb 5? causes conductivity [13] and generates metallic behavior in insulators [14], increases electrical resistivity and enhances hysteresis squareness and fatigue behavior [16,17], decreases the dielectric constant maximum and Curie point [18] and so on. Also, Nb can be considered as a donor dopant for PZT materials [15].…”
Section: Introductionmentioning
confidence: 99%